Population genetic structure and phylogeography of two South Asian Killifishes, Aplocheilus blockii and A. parvus - Sreesha, Gadadharan; Dahanukar, Neelesh; Sudasinghe, Hiranya; Sasikala, G.; Ranasinghe, Tharindu; Wijesooriya, Kumudu; Anoop, V. K.; Thomas, Liju; Meegaskumbura, Madhava; Raghavan, Rajeev (Zootaxa, 2026)
The identity and taxonomic status of the South Asian killifishes Aplocheilus blockii and A. parvus has often been debated, with the latter name considered a junior synonym of the former. To understand whether topotypic A. blockii and A. parvus, and populations across a wider distribution range in peninsular India and Sri Lanka, signal genetic structuring, and to help resolve the ambiguous taxonomy of these nominal species, we studied their population genetics and phylogeography based on the partial mitochondrial cytochrome c oxidase subunit 1 (cox1) gene marker. Phylogenetic analysis revealed that Aplocheilus blockii and A. parvus form two distinct, reciprocally monophyletic sister clades, the former of which is restricted to India while the latter is shared between southern Peninsular India and Sri Lanka. The maximum uncorrected intra-specific cox1 genetic distance was 1.5% for A. blockii and 0.7% for A. parvus, while minimum inter-specific genetic distance between the two species was 2.4%, suggesting that a narrow genetic gap, between 1.5 to 2.4%, separates the species. Despite the low genetic divergence between these sister taxa, they are readily distinguished morphologically by the pattern of iridescent scales on the side of the body. While A. blockii has continuous rows of iridescent scales on the lateral surface, giving an impression of horizontal iridescent lines, iridescence on the lateral surface of A. parvus is restricted to alternate scales, giving an impression of vertical iridescent lines. The median-joining genetic network revealed 37 haplotypes in A. blockii and 32 haplotypes in A. parvus. No haplotypes of A. parvus are shared between southern India and Sri Lanka. Analysis of molecular variance confirmed that there is significant population genetic structuring between the two species and their populations. We discuss genetic diversity and structuring in A. blockii and A. parvus in the context of the physiography of the southern Indian peninsula and Sri Lanka, as well as the historical biogeography of the region, and review implications for the taxonomy of south Asian killifishes.